TINJAUAN BIOMOLEKULER DAN KLINIS OCULAR COVID-19 - Lylys Surjani; Jekson Martiar Siahaan (Majalah Ilmiah METHODA, 2020)
The clinical manifestations of Covid -19 are not only in the airway but are also found in eyes with conjunctival epithelium and ACE-2 receptors as their entry points. The most common clinical manifestation is conjunctivitis, therefore it is not easy to make a diagnosis if it relies on clinical findings because it is similar to a common viral infection. This infection has clinical manifestations in the airway that triggers the immune response leading to a cytokine storm with fatal consequences. There is no specific treatment up to this time. The most important thing is to prevent infection.